Time-course foliar dynamics of poplar short rotation plantations under Mediterranean conditions. Responses to different water scenarios. (April 2022) - Fuertes, A.; Sixto, H.; González, I.; Pérez-Cruzado, C.; Cañellas, I.; Rodríguez-Soalleiro, R.; Oliveira, N.
Abstract: Poplar ( Populus spp.) Short Rotation Coppice (SRC) systems are characterized by high short-term biomass productivity and play a key role in promoting employment in rural areas as well as supplying environmental benefits. However, in the context of climate change with expected reduced water availability in the Mediterranean area, the productivity of these plantations may be seriously limited. In this regard, the aim of this work is to analyse the monthly dynamic responses of relevant variables at foliar level throughout the entire first rotation of a poplar short rotation plantation under two water scenarios: optimal scenario (with irrigation to field capacity (FC)) versus restrictive scenario (with 50% FC irrigation). This data came from 590 trees in a poplar short rotation plantation of the highly productive genotype 'AF2'. LAImax values of 2.39, 7.47 and 9.34 were found for the three-year rotation cycle, pointing to significantly lower values after the establishment year under the restrictive water scenario. SLA mean values displayed a downward trend, with 12.25 m 2 kg −1, 10.82 m 2 kg −1 and 10.47 m 2 kg −1 for years 1, 2 and 3 respectively, no significant differences being observed between water scenarios. NPK foliar concentrations decreased over the rotation, being the values lower under the restrictive scenario. Additionally, the selected genotype, 'AF2', displayed tight stomatal control under conditions of water stress, maintaining high photosynthetic levels. The responses observed in this study can potentially be used to better understand the behavior of these variables which most affect production of poplar plantations in face of climate change. Highlights: Detailed monthly foliar analysis in SRC under two different water scenarios. Significant LAI decrease only after the establishment year in the restrictive scenario. Decreasing SLA trend over years with no significant differences between scenarios. IWUE values significantly greater under water restriction. NPK foliar concentrations and PNUE values decreased over the three years.